Initiation, discontinuation, and restarting HIV pre-exposure prophylaxis: ongoing implementation strategies. Issue 10 (October 2020) - Rutstein, Sarah E; Smith, Dawn K; Dalal, Shona; Baggaley, Rachel C; Cohen, Myron S
Summary: When used appropriately, pre-exposure prophylaxis (PrEP) substantially reduces the risk of HIV acquisition. Early implementation outcomes often suggest poor PrEP adherence and persistence; however, this intervention is time-limited and the need for PrEP fluctuates as risk behaviours change. In this Viewpoint we examine the current guidelines and early programmatic outcomes after starting, stopping, and restarting PrEP, and we review the implications of PrEP in relation to HIV testing algorithms. Guidelines suggest to discontinue PrEP when a person is no longer at risk for HIV, but effectively implementing this strategy requires support tools to make the decision of stopping and restarting PrEP that considers the complex relationship between risk perceptions and risk behaviours. Safely discontinuing PrEP also requires greater understanding of the daily dosing duration that is needed to protect the person after their last HIV exposure. Additionally, clear strategies are needed to re-engage a person as their HIV exposure risk changes over time.